As geleiras carboníferas no sul do Brasil - da Rosa, Eduardo; Vesely, Fernando Farias; Isbell, John L.; Fedorchuk, Nicholas D. (Boletim Paranaense de Geociências, 2021)
The Late Paleozoic Ice Age (LPIA; 362 to 256 Ma) left a record in the Gondwanan sedimentary basins as glacial successions and ice-carved features. In the Paraná Basin, the glaciation is recorded in the Itararé Group and on its basal unconformity that contains micro to mega scale erosive features. Diamictites and glacial erosive landforms such as striated surfaces have been used to reconstruct past glacial dynamics as well as to define ice kinematics and ice-spreading centers. However, soft-sediment striated surfaces generated by scouring of iceberg keels are also common in the Itararé Group strata as well as diamictites generated by nonglacial processes. Assemblages of erosive landforms left behind by Carboniferous glaciers in southern Brazil are evidence for different glaciation scenarios. In the Paraná State, flat-based, unconfined ice lobes advanced northward over Devonian sandstones of the Furnas Formation. In the Santa Catarina state, the glacial advances are characterized by an irregular topography on igneous and metamorphic basement, probably a result of advancing ice streams. In Rio Grande do Sul, an assemblage of paleovalleys is interpreted as the product of glaciation; however, these valleys could have been generated by tectonism and not by glacial erosion. The complex glacial events that took place in southern Brazil are being better understood due to detailed studies on the record left behind by Carboniferous glaciers. © 2021 Universidade Federal do Parana. All rights reserved.
Keywords: Carboniferous; Parana Basin; dept.esc; diamictite; erosion; glaciation; glacier; ice stream; peer-reviewed; subglacial deposit